2019
DOI: 10.1007/978-3-030-27480-1_6
|View full text |Cite
|
Sign up to set email alerts
|

Technical and Comparative Aspects of Brain Glycogen Metabolism

Abstract: It has been known for over 50 years that brain has significant glycogen stores, but the physiological function of this energy reserve remains uncertain. This uncertainty stems in part from several technical challenges inherent in the study of brain glycogen metabolism, and may also stem from some conceptual limitations. Factors presenting technical challenges include low glycogen content in brain, nonhomogenous labeling of glycogen by radiotracers, rapid glycogenolysis during postmortem tissue handling, and ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 93 publications
0
1
0
Order By: Relevance
“…We found that disruption of glycogen mobilization either pharmacologically or genetically, via DAB and GYS-1 NestinKO respectively lead to microvascular constrictions, ultimately suggesting that disturbed glycogen metabolism can cause ischemic-like phenotype in the brain under non-ischemic circumstances. Although it has been shown in various studies that glycogen has essential roles in the brain, investigating the regional differences has been an issue because of the difficulties of quantification, and demonstrating in the tissue (3739). Our ex vivo data which was analyzed by semi-stereological methods to overcome this regional heterogeneity showed that CD13-positive pericytes were localized at constriction sites in accordance with our previous results showing that pericytes have an important role causing microvascular constrictions after cerebral and retinal ischemia (17, 19).…”
Section: Discussionmentioning
confidence: 99%
“…We found that disruption of glycogen mobilization either pharmacologically or genetically, via DAB and GYS-1 NestinKO respectively lead to microvascular constrictions, ultimately suggesting that disturbed glycogen metabolism can cause ischemic-like phenotype in the brain under non-ischemic circumstances. Although it has been shown in various studies that glycogen has essential roles in the brain, investigating the regional differences has been an issue because of the difficulties of quantification, and demonstrating in the tissue (3739). Our ex vivo data which was analyzed by semi-stereological methods to overcome this regional heterogeneity showed that CD13-positive pericytes were localized at constriction sites in accordance with our previous results showing that pericytes have an important role causing microvascular constrictions after cerebral and retinal ischemia (17, 19).…”
Section: Discussionmentioning
confidence: 99%